2020
DOI: 10.1242/dmm.042986
|View full text |Cite
|
Sign up to set email alerts
|

Human embryoid bodies as a 3D tissue model of the extracellular matrix and α-dystroglycanopathies

Abstract: The basal lamina is a specialized sheet of dense extracellular matrix (ECM) linked to the plasma membrane of specific cell types in their tissue context, which serves as a structural scaffold for organ genesis and maintenance. Disruption of the basal lamina and its functions is central to many disease processes, including cancer metastasis, kidney disease, eye disease, muscular dystrophies and specific types of brain malformation. The latter three pathologies occur in the α-dystroglycanopathies, which are caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Characterization of these three LGMDR9 iPS cell lines confirmed pluripotency ( Figures S2 A–S2C), normal karyotype (data not shown), and the presence of a single point mutation in c.826C > A, as shown by PCR and Sanger sequencing ( Figure S2 D). In addition to these novel lines, we also used the recently published iPS cell lines LGMDR9 CDI73, LGMDR9 compound heterozygous FP3 ( Dhoke et al., 2021 ) and B12-57 ( Nickolls et al., 2020 ), and WWS FP4 ( Ortiz-Cordero et al., 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of these three LGMDR9 iPS cell lines confirmed pluripotency ( Figures S2 A–S2C), normal karyotype (data not shown), and the presence of a single point mutation in c.826C > A, as shown by PCR and Sanger sequencing ( Figure S2 D). In addition to these novel lines, we also used the recently published iPS cell lines LGMDR9 CDI73, LGMDR9 compound heterozygous FP3 ( Dhoke et al., 2021 ) and B12-57 ( Nickolls et al., 2020 ), and WWS FP4 ( Ortiz-Cordero et al., 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the recent identification of FKRP as a ribitol-5-phosphate transferase ( Kanagawa et al, 2016 ; Kuwabara et al, 2020 ), the therapeutic effect of ribitol supplementation is under investigation. Recent studies in FKRP mutant mice ( Cataldi et al, 2018 ) and patient-specific iPS cell derivatives ( Nickolls et al, 2020 ; Ortiz-Cordero et al, 2021b ) show the partial restoration of α-DG functional glycosylation upon treatment. An open-label study was announced in March 2021 to determine the safety and tolerability of ascending dose levels of BBP-418 (ribitol) for the treatment of ambulatory and non-ambulatory LGMDR9 patients ( NCT04800874 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is interpreted that the administration of ribitol increases CDP-Rbo production and enhances the enzymatic activity of mutant FKRP thereby improving DG glycosylation. Also, a report suggested that ribitol therapy is effective against the FKRP-L276I mutation, which is most commonly found in patients in Europe and the United States [ 89 ]. Ribitol therapy for FKRP mutation may also require residual FKRP enzymatic activity [ 90 ].…”
Section: Treatment Methodsmentioning
confidence: 99%